PENGARUH MEDIA PERMAINAN TEBAK ANGKA TERHADAP HASIL BELAJAR KOGNITIF PEMBELAJARAN MATEMATIKA DI KELAS II - Julianto, Eko; Aryaningrum, Kiki; Sunedi, Sunedi (JS (JURNAL SEKOLAH), 2024)
Abstract: This study aims to determine the effect of using counting media on the learning outcomes of students at Ulak Kemang 2 Elementary School. This study uses quantitative research in the form of true-experimental with a post-test only control design. Hypothesis testing uses an independent sample t-test. Based on data analysis, it appears that there is a significant effect of the Use of Number Guessing Game Media on Cognitive Learning Outcomes of Mathematics Learning. This can be seen from the calculation of the t-test for mathematics learning outcomes which obtained a Sig. (2-tailed) value of (0.001) ≤ α (0,05) and a t-count value of 3,695 greater than ≥ ttable 2,012. Based on the Decision criteria, Ho is rejected and Ha is accepted so that it is proven that the use of counting media in mathematics learning has an effect on student learning outcomes. Keyword: Learning outcomes; Number Guessing media Abstrak: Penelitian ini memiliki tujuan untuk mengetahui pengaruh penggunaan media alat hitung terhadap hasil belajar siswa SD Negeri 2 Ulak Kemang. Penelitian ini menggunakan penelitian kuantitatif berupa trueexperimental dengan desain post-test only control design. Uji hipotesis menggunakan uji independent sampel t-test. Berdasarkan analisis data, terlihat ada pengaruh yang signifikan dari Penggunaan Media Permainan Tebak Angka Terhadap Hasil Belajar Kognitif Pembelajaran Matematika. Hal ini dilihat dari perhitungan uji t-test untuk hasil belajar matematika yang memperoleh nilai Sig. (2- tailed) sebesar (0,001) ≤ α (0,05) dan nilai thitung sebesar 3.695 lebih besar ≥ ttabel 2,012. Berdasarkan kriteria Keputusan, maka Ho ditolak dan Ha diterima sehingga terbukti bahwa penggunaan media alat hitung pada pembelajaran matematika berpengaruh terhadap hasil belajar siswa. Kata Kunci: Kognitif, media, Tebak Angka